2016
DOI: 10.12669/pjms.325.10755
|View full text |Cite
|
Sign up to set email alerts
|

Effect of half adult dose of oral Rifampicin (300mg) in patientswith idiopathic central serous chorioretinopathy

Abstract: Objectives:To evaluate the effect of half adult dose of oral Rifampicin on mean change in best corrected visual acuity and central macular thickness in patients with central serous chorioretinopathy.Methods:Thirty-eight eyes of 31 patients with idiopathic central serous chorioretinopathy (CSCR) were registered. Unaided Visual acuity, best corrected visual acuity was documented and detailed slit lamp examination along with dilated ophthalmoscopy was performed. All subjects were treated with oral Rifampicin 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Khan et al in their study of 38 eyes in 31 patients prescribed rifampicin 300mg for three months to patients primarily with recent onset CSCR and found that 74% of the patients improved in visual acuity and CMT and also no adverse effects were noted during the study 16. The results in the above study were higher because their 74.2% cases were acute CSCR which usually resolves in 80% of cases without any treatment17,18 but our study included only chronic CSCR and there is significant improvement even after change of regime of the drug.…”
Section: Discussionmentioning
confidence: 96%
“…Khan et al in their study of 38 eyes in 31 patients prescribed rifampicin 300mg for three months to patients primarily with recent onset CSCR and found that 74% of the patients improved in visual acuity and CMT and also no adverse effects were noted during the study 16. The results in the above study were higher because their 74.2% cases were acute CSCR which usually resolves in 80% of cases without any treatment17,18 but our study included only chronic CSCR and there is significant improvement even after change of regime of the drug.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have demonstrated efficacy in chronic CSCR; however, these are limited and non-placebo-controlled. 64,65 In contrast, a recent RCT demonstrated no benefit of rifampin for acute CSCR. 66 Any positive effect of rifampin must also be balanced against its known side effect profile that includes hepatotoxicity.…”
Section: Non-pdt Laser Therapymentioning
confidence: 96%
“…Rifampin is a potent inducer of cytochrome P450 enzymes which can modulate the metabolism of endogenous steroids and has been evaluated as a treatment for CSCR. Some studies have demonstrated efficacy in chronic CSCR; however, these are limited and non-placebo–controlled 64,65 . In contrast, a recent RCT demonstrated no benefit of rifampin for acute CSCR 66 .…”
Section: Systemic Topical and Behavioral Therapiesmentioning
confidence: 99%
“…In addition, Khan et al reported in an observational study on 38 eyes of 31 patients with CSC an improvement in mean BCVA from 0.56 to 0.47 ( p < 0.001) 4 weeks after 300 mg oral rifampicin treatment [ 66 ].…”
Section: Other Oral Pharmacological Treatment Options For Treatingmentioning
confidence: 99%